Artikel Review: Perbandingan Sistem Matriks Hidrofilik dan Sistem Osmotik pada Tablet Lepas Terkendali - Abigail Yemima Christie; Amelia Defina Permatasari; Neza Ardelia Putri; Yola Asri Paramita; Hata Rianti Wasahua (Journal of Educational Innovation and Public Health, 2026)
Controlled-release tablets are designed to release the active substance gradually in order to maintain stable drug plasma levels and reduce the frequency of drug administration. This study aims to compare hydrophilic matrix systems and osmotic systems in controlled-release tablet formulations using a literature review method. The results indicate that the hydrophilic matrix system operates through polymer hydration, diffusion, and matrix erosion mechanisms using polymers such as HPMC and Na CMC, though its release profile is influenced by gastrointestinal physiological conditions. The osmotic system produces a near zero-order release profile that is more consistent and independent of pH changes, despite requiring more complex manufacturing technology and higher production costs. Both systems demonstrate distinct advantages and limitations depending on the drug's solubility, dose uniformity requirements, and target release site. Furthermore, patient compliance and therapeutic efficacy are also key considerations in determining the most suitable formulation approach. Selection of the appropriate system should be tailored to the physicochemical properties of the active substance, therapeutic targets, and production efficiency considerations. A comprehensive understanding of these two systems is essential to support rational formulation decisions and to optimize therapeutic outcomes in pharmaceutical development.